In-Hospital Diagnosis of Tricuspid Papillary Muscle Rupture in an Asymptomatic Patient after Blunt Chest Trauma - C. S. Nabzdyk; M. B. Tabrizi (Case Reports in Critical Care)
Tricuspid papillary muscle rupture after blunt chest trauma is an infrequent injury that often remains undiagnosed until patients become symptomatic months to years after the trauma occurred. It is imperative to diagnose patients early with this condition in order to optimize chances of successful recovery and avoidance of sequelae of long-term tricuspid regurgitation such as atrial fibrillation and right heart failure. Here we describe a case of a 58-year-old man involved in a motocross accident suffering amongst other injuries extensive bilateral rib fractures, hemopneumothoraces, and asymptomatic anterior tricuspid papillary muscle rupture. In addition, a review of the literature and an approach for the workup of trauma patients at risk for blunt cardiac injury are provided.